A Systematic Review and Meta-Analysis of Psychological Research on Conspiracy Beliefs: Field Characteristics, Measurement Instruments, and Associations With Personality Traits - Goreis, Andreas; Voracek, Martin (Frontiers in Psychology, 2019)
In the last decade, the number of investigations of the beliefs in conspiracy theories has begun to increase in the fields of social, differential, and experimental psychology. A considerable number of variables have been suggested as predictors of conspiracy beliefs, amongst them personality factors such as low agreeableness (as disagreeableness is associated with suspicion and antagonism) and high openness to experience (due to its positive association to seek out unusual and novel ideas). The association between agreeableness, openness to experience and conspiracy beliefs remains unclear in the literature. The present study reviews the literature of psychological studies investigating conspiracy beliefs. Additionally, the association between Big Five personality factors and conspiracy beliefs is analyzed meta-analytically using random-effects models. Ninety-six studies were identified for the systematic review. A comprehensive account of predictors, consequences, operationalization, questionnaires, and most prominent conspiracy theories is presented. For meta-analysis, 74 effect sizes from 13 studies were extracted. The psychological literature on predictors of conspiracy beliefs can be divided in approaches either with a pathological (e.g., paranoia) or socio-political focus (e.g., perceived powerlessness). Generally, there is a lack of theoretical frameworks in this young area of research. Meta-analysis revealed that agreeableness, openness to experience, and the remaining Big Five personality factors were not significantly associated with conspiracy beliefs if effect sizes are aggregated. Considerable heterogeneity in designs and operationalization characterizes the field. This article provides an overview of instrumentation, study designs, and current state of knowledge in an effort towards advancement and consensus in the study of conspiracy beliefs.